2018
DOI: 10.1101/434597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct gene-selective roles for a network of core promoter factors inDrosophilaneural stem cell identity

Abstract: Running title: Role of core promoter factors in Drosophila neural stem cell identity. AbstractThe transcriptional mechanisms that allow neural stem cells (NSC) to balance selfrenewal with differentiation are not well understood. Employing an in vivo RNAi screen we identify here NSC-TAFs, a subset of nine TATA-binding protein associated factors (TAFs), as NSC identity genes in Drosophila. We found that depletion of NSC-TAFs results in decreased NSC clone size, reduced proliferation, defective cell polarity and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Some TFIID subunits vary with target genes and cell types (Goodrich & Tjian, 2010). The Drosophila TAF–TRF2 complex has been proposed to perform distinct functions in regulating neural stem cell identity (Neves & Eisenman, 2019). Moreover, previous biochemical studies have shown that both TAF3/BIP2 and TRF2 interact with TAF6 (Weake et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Some TFIID subunits vary with target genes and cell types (Goodrich & Tjian, 2010). The Drosophila TAF–TRF2 complex has been proposed to perform distinct functions in regulating neural stem cell identity (Neves & Eisenman, 2019). Moreover, previous biochemical studies have shown that both TAF3/BIP2 and TRF2 interact with TAF6 (Weake et al., 2009).…”
Section: Discussionmentioning
confidence: 99%